Evaluation of the Role of Potential Biochemical Markers to Assess The Severity of Hospitalized Patients With Covid 19: A Tertiary Hospital Care Study - Sundar Pandey; Shrijana Chapagain (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Coronavirus disease has become a universal health problem and has resulted in millions of hospitalization and deaths. Coronavi- rus is a multi-system infection predominantly affecting the respiratory system, resulting in various hematological and biochemical alterations reﬂected in various investigations. Multitudes of research establishing the role of biomarkers in coronavirus infection are ongoing globally. This study aimed at studying the common biochemical markers like CRP, LDH, and D-dimer to access the severity of the disease and hospital outcome. MATERIAL AND METHODS This was a retrospective cross-sectional study performed at a tertiary care hospital in western Nepal among RT-PCR-positive ICU patients who were ≥ 18 years for a period of six months (May 1 to October 30, 2020). Demographic, clinical, and laborato- ry data were collected from hospital records and the results were analyzed. RESULTS Among 110 admitted patients, 56 were females and 54 were males. The mean age of presentation was 56.5 years. Shortness of breath, cough, and fever were the main presenting complaints. CRP was high in 95% of patients, LDH in 94.5%, and D-dimer in 81.67% of patients. Mechanical ventilation was required in 19.9%, complications were observed in 67.27% and in-hospital mortality was 11.6%. The most common cause of death was acute respiratory distress syndrome. CONCLUSION Biomarkers like CRP, LDH, and D-dimer can be used for stratifying coronavirus disease patient’s severity and clinical outcome which may later be helpful in identifying risk patients and taking immediate actions in terms of treatment, care, and evaluation.